THE ROLE OF ACOUSTIC DESIGN IN ENHANCING SUSTAINABILITY IN IRAQI SECONDARY SCHOOLS: MADIHA AL-BIRMANI SCHOOL IS A CASE STUDY - Nada Abdul-Ameer Mubarak; Beshaer M. AL- Shimmery; WED THAMER ABDULAALI (Journals Park Publishing, 2025)
The design of buildings in general and schools in particular requires a careful consideration of the impact of the design on sound clarity in a way that helps in avoiding acoustic problems such as noise, echo, etc. Therefore, emphasis must be placed on achieving auditory comfort and providing a good study environment in the classrooms. To achieve this, the architect must be innovative and thoughtful, planning and designing to achieve a sustainable environment that maintains environmental balance without compromising the divine balance created by the Lord of the Worlds. For that, and taking into consideration the importance of sound in the success of the teaching and educational process in our schools in Iraq, it is important to shed light on schools designing and find sustainable solutions without using energy sources. Based on the importance of the topic of sound, the researcher explains in the current study the effect of using sustainable materials in reaching acoustic comfort. To achieve this, the researcher chose a classroom in one of the distinguished schools in Iraq as a sample for research and studied it to identify audio problems and find appropriate solutions for them. The researcher resorted to audio analysis using the Odeon program to calculate sound intensity. She introduced different changes to the endings in the Odeon program and measured the sound intensity for each change separately. At the end of the study it was found that changing the ceiling finishes had the greatest impact in reducing acoustic problems. Based on these conclusions, some recommendations and specific suggestions were put forward.
Keywords: Sustainable acoustic design, classrooms, sound, sound intensity, sound frequency, acoustic problems.